2018
DOI: 10.22456/1679-9216.15282
|View full text |Cite
|
Sign up to set email alerts
|

Intussuscepção jejunoileal dupla em um cão

Abstract: Intussuscepção é uma afecção digestiva relativamente comum na clínica veterinária. Caracteriza-se pela invaginação de um segmento intestinal em outro adjacente, de maneira anterógrada ou retrógrada. No presente estudo descreve-se um caso de intussuscepção jejunoileal dupla em um cão. Os sinais clínicos são inespecíficos e incluem vômito, dor abdominal, fezes mucóides e sanguinolentas e pela existência de massa abdominal palpável. O diagnóstico se dá pelos sinais clínicos e exames complementares, como radiograf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…The intussusception may affect all segments of the digestive tract in animals: esophagogastric and gastroduodenal (Bercier et al 2017), duodenoduodenal (Cappua and colleagues, unpublished), jejunojejunal (Firmino et al 2017), jejunoileal (Colomé et al 2006), ileocolic (Wosar and Lewbart 2006), ileocecocolic (Firmino et al 2017), and colocolic (Hasse et al 2019). The type of intussusception observed in our study was colocolic.…”
Section: Discussionmentioning
confidence: 99%
“…The intussusception may affect all segments of the digestive tract in animals: esophagogastric and gastroduodenal (Bercier et al 2017), duodenoduodenal (Cappua and colleagues, unpublished), jejunojejunal (Firmino et al 2017), jejunoileal (Colomé et al 2006), ileocolic (Wosar and Lewbart 2006), ileocecocolic (Firmino et al 2017), and colocolic (Hasse et al 2019). The type of intussusception observed in our study was colocolic.…”
Section: Discussionmentioning
confidence: 99%
“…É indicada a realização de 48 horas de jejum de alimentos sólidos, a dieta líquida deve ser introduzida 24 horas após a cirurgia e em seguida deve introduzir dieta pastosa (Colomé et al, 2006). No caso descrito foi instituído jejum de 24 horas de alimentação líquida, pois o animal permaneceu internado e em seguida foi introduzido aos poucos água de coco e introduzido comida pastosa cinco dias após a cirurgia.…”
Section: Discussionunclassified
“…Estrangulamento ocorre pela interrupção de fluxo adequado de sangue de um órgão, ocasionando necrose caso não seja feita a intervenção cirúrgica (Crespo et al, 2001). Em casos de estrangulamento, pode ocorrer obstrução do sistema gastrointestinal, e alguns sinais clínicos frequentemente relacionados são a dor abdominal, apatia, anorexia e em casos graves vômito e fezes com sangue (Colomé et al, 2006;Ramírez et al, 2015).…”
Section: Introductionunclassified
“…Even though most cases have idiopathic origin (Baral 2015;Levitt & Bauer, 1992;Patsikas et al, 2003), such as double intussusception as reported by Colomé et al (2006), Valiei & Beheshti (2011) and Kim et al (2012), predisposing factors can be associated with the appearance of this disease in young animals, including intestinal parasitism (Baral, 2015). In severe cases, although rare, those parasitoses can cause intense diarrhea and exacerbation of intestinal peristalsis, causing strong contractions that can cause part of the intestine to penetrate into the lumen of the adjacent intestinal segment (Diniz et al, 2004;Ferreira et al, 2013;Dubey, 1993;Tafti, 1999).…”
Section: Discussionmentioning
confidence: 99%